Metamorfoze bh. suvereniteta / The Metamorphosis of BH Sovereignty: Od troipostoljetnog suvereniteta do ZAVNOBiH-a i referenduma o nezavisnosti Bosne i Hercegovine / From the Three Hundred and Fifty Years Long Sovereignty to ZAVNOBIH and the Referendum on Independence of Bosnia and Herzegovina - Bečirović, Fikret (Pregled: časopis za društvena pitanja / Periodical for social issues, 2016)
Taking into regard the crucial facts in the acquisition and development of Bosnia and Herzegovina through the turbulent course of its history, one can rightly conclude that it is about a country with too little geography and too much history, a country placed at the crossroads of the worlds and constantly affected by big powers, the country that has been since the beginning of time influenced by cultural, political and religious waves, and taken by conquerors of different races, religions and ideologies. In such political environment, in relations of political influence in the acquisition, development, lost, recovery, as well as erosion of the state sovereignty, there are elements of the overall national, cultural, religious and any other constituents of the Bosnian being in such polychromic metamorphosis. In this sense, at the debate on the subject ” The Sovereignty of the State of Bosnia and Herzegovina” of 25 February 2016, organized by the “Pregled” Journal‟s Board of Editor to mark the occasion of 24th anniversary of the Referendum on independence and sovereign Bosnia and Herzegovina, I tried to give my contribution by focusing and emphasizing on the forms of Bosnian statehood that in different time periods and forms of political authority had qualitatively different forms of sovereignty and identity. One question was permeating throughout this long way of development, both in periods of full and limited the sovereignty of foreign rule, “To whom Bosnia belongs?” Of course, that question was raised without taking into regard BH personal sovereignty, integrity and its nation(s). In this sense, the paper attempts to focus on certain milestones and reminiscences of Bosnian sovereignty and identity, as well as its attempts to deny, endanger, perfidiously and brutally dilute it, as it was done in the Dayton Peace Accords and continuing to divide Bosnia and Herzegovina in a perfidious manner.